Scrum-Driven Task Management for University IT Governance: A Multi-Role Usability Evaluation - Muhammad Faried Saputra; Aris Budianto (Engineering Science Letter, 2026)
Task management is an essential aspect of organizational operations that involves coordinating various work activities and facilitating collaboration among team members. However, in many organizations, task management processes are still carried out through informal communication channels such as direct conversations, email, or instant messaging applications, which complicate task monitoring and documentation. This study aims to develop a web-based task management system that supports more structured task management within the Directorate of Information and Communication Technology at Universitas Sebelas Maret. The system was developed through four iterative Scrum sprints over 10 weeks. Functional testing employed the Black-Box Testing method, and usability was assessed using the System Usability Scale (SUS) with 20 purposively selected respondents across four user roles: administrators, sub-directorate heads, section heads, and staff members. The results indicate that all system functions operated successfully, and the system achieved an average SUS score of 75.25 — categorized as Good and exceeding the standard usability benchmark of 68, with scores ranging from 71.0 (section heads) to 81.0 (administrators). These findings suggest that Agile Scrum-based development produces task management systems that are adaptive to organizational needs and well-accepted across hierarchical user roles, with implications for IT governance practice in higher education institutions.